«Talgenism» in the Digital Age: A Domestic History of cMOOC - M. A. Babaeva; E. B. Golubev (Moscow Polytechnic University, 2020)
The authors consider the questions of the transformation of educational space in the modern digital era. They focus on the weakness of the theoretical foundation of e-learning in the context of mass practice of its implementation and application and discuss the legitimacy of applying traditional theories to e-learning in a radically changed educational space and the need to develop a new theory. Cognitivism, constructivism, and behaviorism are the basis of the traditional pedagogical system (class-lesson in school and lecture-seminar in universities). It is shown that a different pedagogical system is represented by connectivism - the theoretical construction of G. Siemens who created it as a "theory of the digital age." On the basis of connectivism and for its study, G. Siemens and S. Downs have developed the first massive open online courses (cMOOC) - and this theoretical design was put into practice. One more learning technology similar to the connectivism was discovered, which is also based on a pedagogical system different from the traditional one. This made it possible to give the "learning theory of the digital age" a noticeable "historical volume". The roots of the modern connectivism of massive open online courses have been discovered in Russia. One hundred years ago, the famous teacher Alexander Rivin for the first time realized the idea of collective mutual learning. This method which he called "talgenism" (a derivative of "talent" and "genius") relied on "dialogical communication" in variable pairs and allowed to achieve incredible results in the joint training of people of different ages and different levels of training. The article traces the historical milestones of the development of the method of collective mutual learning in Russia and adduces the documentary evidence of experiments on the creation of a fundamentally different pedagogical system. The authors argue that the method of collective mutual learning (talgenism) of the Russian teacher A.G. Rivin and the technology of modern connectivism implemented in the massive open online courses with cMOOC of Canadian researchers G. Siemens and S. Downs have common key features. Despite the time and geographical gap (Russia, 1918 and Canada, 2008), each of these technologies makes it possible a fundamentally new learning process focused on the needs of a student, the organization of which is practically unattainable with a traditional class-lesson or lecture-seminar system. Both technologies are presented as effective practical implementations of the new education paradigm, which allows us to carefully and comprehensively study its elements. A conclusion is drawn on the prerequisites for the creation of a new learning theory which would become the foundation for a new time alternative pedagogy which could claim the status of a general theory, a base not only for distance, electronic, but also for classroom learning.